Transformasi Akuntansi Keberlanjutan di Sektor Publik melalui Digitalisasi: Menuju Tata Kelola Berbasis ESG - Rina Komala; Layali Ihyani; Widia Febriana (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2026)
The advancement of sustainability accounting within the public sector is becoming an increasingly important issue, driven by the rising demand for transparency, accountability, and management of public resources focused on sustainability. This research seeks to examine how digitalization contributes to the adoption of accounting that incorporates Environmental, Social, and Governance (ESG) principles across various public sector entities. The methodology employed is a descriptive qualitative approach, utilizing a literature review and an analysis of the implementation practices of digital systems in several governmental organizations. Findings indicate that leveraging digital technologies, including cloud computing-based accounting information systems, big data analytics, and integrated reporting platforms, can enhance the quality of sustainability information, making it available more swiftly, accurately, transparently, and in a more accessible manner. The incorporation of ESG indicators into.